Adsorption of Copper, Zinc, Chromium and Nickel Using Plantation crop waste as Adsorbents in Contaminated Soil - Guruprashanth N; Udaykumar G (International Journal of Management, Technology and Social Sciences (IJMTS), 2024)
This study investigates the adsorption behaviour of copper, zinc, chromium and nickel on plantation crops such as Arecanut husk (AH) and Coconut husk (CH) using a batch technique. Key parameters affecting the adsorption phenomenon were contact time, initial metal ion concentration, and temperature. The results showed equilibrium was reached within four hours, with adsorption capacity being temperature-dependent and endothermic. Efficiency of removal was maximum at lower concentrations, while adsorption capacity improved at higher concentration. Freundlich and Langmuir models are appropriate for predicting the adsorption isotherm. At 300C, the maximum adsorption of Cu, Zn, Cr and Ni on AH and CH were 0.95 mg/g, 1.27 mg/g, 0.78 mg/g, 0.88 mg/g, 1.22 mg/g, 1.64 mg/g, 1.66 mg/g, and 1.69 mg/g respectively. CH exhibited higher removal and adsorption capacities than AH, with zinc showing the strongest adsorption attraction, following the order Cu < Ni < Cr< Zn for plantation crop types of adsorbents.